2017
DOI: 10.5812/ircmj.55943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epidermal Growth Factor, Glial Cell Line-Derived Neurotrophic and Leukemia Inhibitory Factor on the Proliferation and Differentiation Potential of Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Background: There is a great deal of interest in using adipose tissue-derived mesenchymal stem cells (AT-MSCs) for clinical applications. However, the important limitations of clinical application of stem cells are the small number of cells and their differentiation into undesirable lineage in vitro. To overcome this problem, various growth factors are studied extensively. Objectives: The current study aimed at using 3 different doses of epidermal growth factor (EGF), glial cell line-derived neurotrophic (GDNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…The pattern of CD marker expression was similar to the MSCs. CD90 and CD44 were overexpressed in the isolated cells, but the expression of the CD31 and CD45 was low, as found in the previous study (Eliyasi Dashtaki et al, 2018).…”
Section: Isolation and Culture Of The Mscssupporting
confidence: 85%
See 2 more Smart Citations
“…The pattern of CD marker expression was similar to the MSCs. CD90 and CD44 were overexpressed in the isolated cells, but the expression of the CD31 and CD45 was low, as found in the previous study (Eliyasi Dashtaki et al, 2018).…”
Section: Isolation and Culture Of The Mscssupporting
confidence: 85%
“…To increase the efficiency of the differentiation, studies are performed to provide a suitable niche for stem cells. In our previous study, three different doses of EGF, GDNF and LIF were added to the culture of AT-MSCs and it was observed that the viability of the cells in the presence of EGF (10 ng/ml), GDNF (5 ng/ml) and LIF (5 ng/ml) was increased (Eliyasi Dashtaki et al, 2018). As we previously reported that the mice transplanted with AT-MSCs supplemented with the aforementioned growth factors showed more expression of Mvh and Gcnf compared to the mice transplanted with cells, cultured in medium without growth factors (Eliyasi Dashtaki et al, 2020).…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Cell and Developmental Biology frontiersin.org (Abdelaziz et al, 2019;Elbaghdady et al, 2018;Sherif et al, 2018), and testicular injection also has an improvement effect (Hsiao et al, 2015;SM et al, 2017). ADSCs and AFSCs can reduce oxidative stress in the testes and promote sperm production, (Eliyasi et al, 2020;Ibrahim et al, 2021;Qian et al, 2020;Siregar et al, 2021), and can improve the damage of chemotherapy drugs to testes (Meligy et al, 2019). Intratesticular injection of ADSCs can improve the spermatogenesis of azoospermia (Ganjibakhsh et al, 2022;Hajihoseini et al, 2018;Karimaghai et al, 2018), while xenotransplantation of human umbilical cord blood derived MSCs into azoospermia mice also has the same effect (Abd et al, 2017).…”
Section: Mscs In Male Infertilitymentioning
confidence: 99%
“…The molecular weight of EGF is about 6000 Da, and the isoelectric point of EGF is 4.6 [13]. EGF participated in various physiological activities, such as cell division, proliferation, and migration [14][15][16][17]. It could promote the growth of epidermal cells, epithelial tissue regeneration, and wound healing, which had been widely used in the clinical treatment of skin wounds [18][19][20].…”
Section: Introductionmentioning
confidence: 99%